Intraseasonal variability of the West african monsoon : characterization and modelling - (:unkn) unknown (My University, 2010)
The intraseasonal variability of the West African Monsoon is associated with persistent dry and wet periods over the Sahel, whose consequences can be dramatic for local populations. Its understanding, modelling and forecast still pose a challenge to the scientific community, notably because it involves a large number of space and timescales. The present study elaborates a few answers to these issues. The Saharan heat low is one of the major actors of the African monsoon. The characterization of its intraseasonal variability revealed the existence of interaction between the tropics and the extratropics, at the 15-day timescale. As it propagates eastward above the Atlantic and the Mediterranean, a Rossby wave train modulates the heat low ventilations, and thus its structure. Anomalous circulation, as well as temperature and humidity anomalies, can be induced over the Sahel, and lead to intraseasonal modulations of convection, especially to those, which originate from the Eastern Sahel, and which, then, propagate westward. Current state-of-the-art (CMIP3) climate models still have significant problems and display a wide range of skill in simulating the West African monsoon mean state and intraseasonal variability. The high frequency variability is particularly difficult to capture. However, the account for processes, which inhibit convection development, may be expected to be an important step in the improvement of the monsoon modelling and the forecast of its intraseasonal fluctuations
Keywords: African Research